VARIATION OF SOME WATER QUALITY PARAMETERS OF HUWAIZA MARSH IN SOUTHERN IRAQ (Journal of Engineering, 2012)
Huwaiza marsh is considered the largest marsh in the southern part of Iraq. It is located between 31° and 31.75° latitude and extends over the Iraqi-Iranian border; but the largest part lies in Iraq. It is located to the east of Tigris River in Messan and Basra governorates.In this research, the variation of some water quality parameters at different locations of Huwaiza marsh were studied to find out its efficacy in the treatment of the contamination coming from the wastewater outfall of Kahlaa brokendown sewage treatment plant which lies on the Kahlaa River. This rive is the main feeder of Huwaiza marsh. Ten water quality sampling locations were chosen in this marsh. The water samples were taken during 2009 for three months; January, April and August representing winter, spring and  summer respectively.The results of water quality analyses showed that Kahlaa untreated sewage had a negative impact on the water quality of Huwazia marsh; especially in its upstream region. Analyses of water samples taken from the middle and downstream end of the marsh showed that the marsh water is safe for fishing and swimming in these regions.